FAKTOR YANG MEMPENGARUHI FIRM VALUE - Angelia, Vanessa; Nugroho, Vidyarto (Jurnal Paradigma Akuntansi, 2025)
This study aims to determine the effect of investment decisions, financing decisions and dividend policy on firm value in banking companies listed on the Indonesia Stock Exchange (IDX) during 2017 – 2021. This research used purposive sampling technique in taking samples with valid data that can be used as many as 7 companies. Data processing in this study uses multiple regression analysis techniques and is assisted by SPSS 26 and Microsoft Excel 2020 software. The results of this study are that there is a significant positive effect between the investment decision variables and dividend policy variables with the firm value variable, while the funding decision variable has no effect on the value of the company. The implication of this research is the need for planning in making investment decisions, financing decisions and dividend policies in order to increase firm value